The problem with stigma: identifying its impact on drug users and recommendation for interventions: Musuh dalam selimut: identifikasi dampak stigma bagi pengguna narkoba serta intervensi yang dibutuhkan - Rina Apriliani Sugiarti (Talenta Publisher, 2023)
Treatment for substance use cannot separated from stigma problems. Stigma is prevalent and causes negative impacts on stigmatized groups and rehabilitation outcomes. This study aimed to identify the problem with stigma and find recommendations for intervention to reduce the stigma that has been tested for efficacy. The method used is a literature study using bibliographic annotation data analysis. The result of the study is that stigma is detrimental and occurs at an individual social and structural level that is found in policy, regulations, and health professional's and law enforcement's attitudes toward drug users.